A Mixed-Methods Investigation of Unmet Needs, Symptom Experiences, and Quality of Life in Individuals Living with Idiopathic Pulmonary Fibrosis - Bramhill, Carita Roberta (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2026)
Title: A mixed-methods investigation of unmet needs, symptom experiences, and quality of life in individuals with idiopathic pulmonary fibrosis. Background and Aim: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, interstitial lung disease characterised by declining lung function and impaired quality of life. The burden on the healthcare system is expected to intensify given the global rise in the incidence and prevalence of idiopathic pulmonary fibrosis, and ongoing improvements in median survival among those receiving antifibrotic medication. Within this context, there is an urgent need to identify and address the unmet needs of those with IPF to ensure equitable, standardised, and patient-centred care. This study aimed to explore the unmet needs, symptom experiences, and quality of life of individuals diagnosed with IPF. Methodology: A sequential explanatory mixed-methods design was employed, underpinned by pragmatism, which provided the philosophical approach, and guided by the Levesque healthcare access theoretical framework. Methods: Phase one involved an audit of healthcare professionals (N = 16) recruited from five national hospital sites. Phase two surveyed individuals diagnosed with IPF (N = 237) using validated instruments, including the St. George Respiratory Questionnaire-IPF (SGRQ-IPF), IPF Patient-Reported Outcome Measure (IPF-PROM) and the Lung Information Needs Questionnaire (LINQ). Phase three consisted of semi-structured interviews (N = 20) to gain deeper insights into unmet needs, symptom experiences, and quality of life. Findings: Barriers to healthcare access were prominent, with significant challenges in referral to lung transplantation assessment, pulmonary rehabilitation, counselling, and clinical trials. Multidisciplinary team (MDT) provision varied significantly, with notable geographical disparity in equitable access to key supports. Palliative care discussions were often delayed or absent, limiting opportunities to plan for end-of-life care preferences. The most frequently reported symptoms were breathlessness, cough and fatigue. Poorer quality of life was significantly associated with female gender, oxygen use, lack of health insurance, employment disruption, living alone and having a comorbid condition. Participants also reported difficulties with obtaining an accurate diagnosis, navigating the healthcare system, and coping with the psychosocial impacts of IPF, including isolation, uncertainty and financial strain. Male participants and those living alone had higher information needs. Coping strategies were largely self-directed, involving family support, peer engagement and activities such as exercise, yoga and singing. Discussion and Conclusion: This study highlights the substantial symptom burden and wide-ranging unmet needs experienced by individuals with IPF. Addressing gaps requires a multifaceted approach, including improved public awareness, early diagnosis, timely information provision, enhanced access to palliative care, pulmonary rehabilitation and lung transplantation assessment, self-management for symptoms, improved retention and better MDT resourcing. The implementation of a national registry, alongside innovative strategies such as enhanced peer support and social prescribing, is essential to optimise quality of life and inform further policy, research and service planning.
APPROVED
Keywords: IPF; Unmet Needs; Quality of Life; Idiopathic Pulmonary Fibrosis